Prezbiterat w służbie komunii w świetle posoborowego nauczania Kościoła - Biela, Bogdan (Studia Pastoralne, 2026)
Contemporary ecclesiology postulates: „the Church as communion might be more clearly understood and concretely incorporated into life” (The Final Report of the Extraordinary Synod). This idea should pervade all actions of presbyters and influence a new style of priesthood. This is confirmed both by post-council teaching of the Church and the teaching of the Church in Poland. It was particularly developed in a post-synodal exhortation Pastores Dabo Vobis (1992) in which John Paul II emphasised that „the ecclesiology of communion becomes decisive for understanding the identity of the priest, his essential dignity, and his vocation and mission”. Other documents of Magisterium Ecclesiae followed this direction. Three documents of the Congregation for the Clergy deserve special attention: Directory on the Ministry and Life of Priests (1994), a letter The Priest and the Third Christian Millennium, Teacher of the Word, Minister of the Sacraments and Leader of the Community (1999) and an instruction The Priest, Pastor and Leader of the Parish Community (2002). Among Polish documents there are two written by the Second Polish Plenary Synod that deserve special attention: Needs and Tasks of a New Evangelisation at the Break of the Second and the Third Christian Millennium and Priesthood and Consecrated Life as Community of Life and Ministry with Christ. The documents emphasise that a priest should always remember that he „sanctifies himself by his care for a community which had been entrusted to him. This care should be manifested in being with a community and in a community”. Therefore the synod suggests that „in nominating parish priests one should take into account not so much and not only seniority and achievements but practical pastoral skills, especially the ability of team-work and a social sensitivity”.